Globalization, Environmental Damage and the Corona Pandemic – Lessons from the Crisis for Economic, Environmental and Social Policy - Bianca Blum; Bernhard Neumärker (Albert-Ludwigs-Universität Freiburg, Freiburg Institute for Basic Income Studies (FRIBIS), 2020)
The rapidly expanding corona pandemic in 2020 has largely brought the world to an economic stagnation. The impact on the environment, especially on air quality, from almost suspended air traffic, idle industry and economic lockdown is enormous, but also the economic and social consequences of the crisis. This state of stagnation hardly appears to be economically and socially sustainable. However, we should ask ourselves right now what we can learn from the situation in order to question globalization, better intercept future comparable crisis situations and take the step towards more sustainable development on an ecological, economic and social basis. The paper identifies the areas of externality management to improve environmental quality, digitalization and network expansion as well as basic income as central concepts that need to be addressed in and after the crisis. Concrete concepts are suggested and discussed at the end of the paper. – – Die schnell wachsende Corona Pandemie im Jahr 2020 hat die Welt weitgehend in eine wirtschaftliche Stagnation gebracht. Die Auswirkungen des fast unterbrochenen Flugverkehrs, der stillgelegten Industrie und des wirtschaftlichen Lockdowns auf die Umwelt, insbesondere auf die Luftqualität, sind enorm; aber auch auf die wirtschaftlichen und sozialen Folgen der Krise. Dieser Stillstand scheint wirtschaftlich und sozial kaum nachhaltig zu sein. Wir sollten uns jedoch jetzt fragen, was wir aus der Situation lernen können, um die Globalisierung in Frage zu stellen, zukünftige vergleichbare Krisensituationen besser abzufangen und den Schritt zu einer nachhaltigeren Entwicklung auf ökologischer, wirtschaftlicher und sozialer Basis zu gehen. Das Arbeitspapier identifiziert dabei die Bereiche des Externalitätenmanagements zur Verbesserung der Umweltqualität, Digitalisierung und Netzerweiterung sowie des Grundeinkommens als zentrale Konzepte, die in und nach der Krise angegangen werden müssen. Konkrete Konzepte werden am Ende des Papiers vorgeschlagen und diskutiert.
Keywords: H12; H23; H53; 330; corona crisis management; basic income; environmental politics; pandemics; globalization; public policy